HTML5 programming with JavaScript for dummies - Mueller, John, 1958- (--For dummies., 2013)
Web designers and programmers, add JavaScript to your HTML5 development toolkit without fear Modern websites are complex, and some of the most exciting features - things like geolocation, canvas, portability to mobile and more - require JavaScript to leverage what HTML5 can create. Don't know JavaScript? That's where HTML5 Programming with JavaScript For Dummies comes in. Rather than walking you through JavaScript as a programming language, it approaches JavaScript as a tool to help you enhance web pages. Helps web designers and programmers tap the full power of HT.